Determinants of Audit Judgment with Task Complexity As Moderating Variable - Muhammad Adil; Sri Sundari; Muhammad Irdam Ferdiansah; Ayu Puspitasari; Anisatun Humayrah Rais (Universitas Muhammadiyah Sorong, 2022)
he purpose of this study was to determine the determinants of Audit Judgment with task complexity as a moderating variable. This study uses a quantitative approach by distributing questionnaires to accountants who work at KAPs in Makassar City. The sample in this study were 32 auditors. Data were collected from distributed questionnaires and tested with SPSS22. The findings of the research show that professionalism, independence, and positive experience significantly affect audit judgment. Task complexity is able to moderate the relationship between professionalism and experience with audit judgment, and task complexity is not able to moderate the relationship between independence and audit judgment.